2016
DOI: 10.1177/0706743716643741
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Psychiatric, Psychological, and Behavioural Outcomes following Mild Traumatic Brain Injury in Children and Adolescents

Abstract: Background: Evidence regarding longer-term psychiatric, psychological, and behavioural outcomes (for example, anxiety, mood disorders, depression, and attention disorders) following mild traumatic brain injury (mTBI) in children and adolescents has not been previously synthesized. Objective: To conduct a systematic review of the available evidence examining psychiatric, psychological, and behavioural outcomes following mTBI in children and adolescents.Materials and Methods: Nine electronic databases were syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
105
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 68 publications
4
105
0
1
Order By: Relevance
“…For many years in the literature, there has been a consistent link between adult concussion from contact sports (hockey, American football, boxing, rugby) and major depressive disorder,9–11 generalised anxiety disorder8 12 13 and suicide 14–16. More recent literature indicates a correlation between sports-related concussion and novel psychiatric diagnosis in a paediatric population 17. Studies also indicate more serious long-term and short-term effects in youth compared with adults 18–25…”
Section: Introductionmentioning
confidence: 99%
“…For many years in the literature, there has been a consistent link between adult concussion from contact sports (hockey, American football, boxing, rugby) and major depressive disorder,9–11 generalised anxiety disorder8 12 13 and suicide 14–16. More recent literature indicates a correlation between sports-related concussion and novel psychiatric diagnosis in a paediatric population 17. Studies also indicate more serious long-term and short-term effects in youth compared with adults 18–25…”
Section: Introductionmentioning
confidence: 99%
“…a further systematic review of 30 studies examining children's (< 19 years) psychological, psychiatric and behavioural outcomes following mild tBi found higher rates of hyperactivity and inattention. 6 The authors concluded that most children recover quickly, but a small proportion have persistent problems. Prospective longitudinal studies evaluating children's recovery over time were recommended.…”
mentioning
confidence: 99%
“…Prospective longitudinal studies evaluating children's recovery over time were recommended. 6 With increasing numbers of children with mild tBi presenting for treatment, 7 continuing controversy surrounding the nature of children's recovery 8 has done little to alleviate the challenges faced by community-based, healthcare providers. These challenges can be ameliorated by accurate information about paediatric outcomes, and identifying factors associated with recovery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…I disclose that I am also privileged to be a contributing author on both of the TBI articles. 1,2 The 2 articles that focus on TBI in this edition are review articles of conditions of high public health concern. Public awareness of adult sports-related TBI has risen in the past few years, especially in the arena of football.…”
mentioning
confidence: 99%